Witnesses and Victims in the Criminal Justice System - Michael Laurenscius (LEGAL BRIEF, 2018)
Although Indonesia already has Law no. 13 of 2006 concerning Witness Protection and but formally, this law is still considered to be not optimal in regulating the protection of witnesses and victims because there are still deficiencies here and there. The nature of the research used is descriptive and the type of research used is normative juridical research, namely research that uses statutory regulations as the basis for solving the problems raised. The data used is secondary data and the data collection method used in this study is library research. The data analysis used is qualitative data. Regulations relating to the authority of the witness and victim protection agency (LPSK) are contained in Law no. 13 of 2006, Regulation of the Witness and Victim Protection Agency of the Republic of Indonesia Number 1 of 2011 concerning Guidelines for Protection Application Services at Witness and Victim Protection Institutions, and Government Regulation Number 44 of 2008 concerning Compensation, Restitution and Assistance to Witnesses and Victims. Before the LPSK provides its protection, witnesses and / or victims must submit a request to meet the requirements set by the LPSK, which sometimes it is hard for witnesses and victims to do so. Providing security and safety guarantees for witnesses and / or victims, can make them feel safe and comfortable so that they can testify and provide information that can help people uncover an organized crime. Witnesses and / or victims are entitled to personal protection, family and property. Witnesses and / or victims are also entitled to receive medical and psychological assistance and can apply for restitution (compensation). In addition to the above rights, witnesses and / or victims will also be accompanied by the LPSK at every examination at the Police or at court. This is done to provide a sense of security and comfort to witnesses and / or victims. So they can testify with comfort.